Challenges and Prospects of Social Security Services for Small Industry Laborers in District Bahawalpur (Al-Qamar, 2024)
Social security provisions constitute a fundamental element of a welfare state. These benefits safeguard the rights of the working class by offering financial assistance to meet necessities. The efficiency of laborers in industrial settings positively correlates with the availability of social security benefits. The increased endowment of these services enhances the laborers' capacity to perform effectively within factories. The Punjab Small Industries Corporation in Bahawalpur was established to generate employment opportunities for individuals and to augment the production of various goods. It has been estimated that three thousand nine hundred sixty-three laborers are currently employed in these industries. This research study investigates the actual circumstances and challenges laborers face concerning their social security entitlements. A sample of 198 participants was obtained utilizing a proportionate random sampling methodology. During the data collection phase, 177 laborers were present. The interview schedule was meticulously crafted to incorporate open-ended and closed-ended questions as a research tool. This study reveals that laborers engaged in small industries within the Punjab region, specifically in Bahawalpur, possess an awareness of the social security services offered by numerous organizations. However, the laborers also indicated that the process of accessing social security services is exceedingly intricate and that the quality of these services is inadequate. Consequently, the laborers expressed reluctance to utilize social security services due to the substandard nature of the services provided. Therefore, it is recommended that measures be implemented to address the issues related to procedural delays in the delivery of social security benefits to laborers. This would enable laborers to experience satisfaction and concentrate fully on their occupational responsibilities.
Keywords: Social Security Services; Laborers; Small Industries; ublic Assistance; Social Insurance